Communication – Conflicts – Alternative Techniques – As A Good Example of the Supportive Role of Communication in the Fight Against Bullying and as a Tool of Early Problem Recognition - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
An important prerequisite for the applicability of children’s rights is the recognition of the fact of the violation and the possession of the necessary knowledge. Children’s communities – partly due to the lack of information and partly due to peer (group) pressure – are often accepting of offensive, verbal, psychological or physically abusive behaviour. In addition to the family, school provides the most decisive medium for the socialization process, so it would be very important if teachers also reacted with sufficient sensitivity to forms of behaviour that endanger children’s rights, with the aim of early problem recognition. Creating an atmosphere of trust with children makes it possible to involve communication-focused methods that help solve problems, resolve conflicts by involving the affected community - and convey clear messages to children. These experiences are not only important in connection with resolving a specific situation or with setting an example, but also because they enable students to behave assertively, to take action against peer abuse, to strengthen their empathetic skills and ultimately contribute to the more effective exercise of their children’s rights.Keywords: school violence, bullying, peer-groups, teacher-student conflict, early problem recognition, mediation, facilitation, alternative conflict resolution